Report on the institutional and regulatory differences between the American and European securitization markets - Adam J. Levitin (Sachverständigenrat zur Begutachtung der Gesamtwirtschaftlichen Entwicklung, 2023)
This Report, commissioned by the German Council of Economic Experts (Der Sachverständigenrat zur Begutachtung der gesamtwirtschaftlichen Entwicklung), addresses the key institutional and regulatory differences between the American and European securitization markets. In particular, it considers the way the American and European regulatory systems have responded to moral hazard concerns in securitization, and it examines potential factors constraining the European securitization market after the Global Financial Crisis.
Keywords: 330